Binaries discovered by the SPY project: V. GD687 - A massive double degenerate binary progenitor that will merge within a Hubble time - Geier, Stephan; Heber, Ulrich; Kupfer, Thomas; Napiwotzki, R. (Astronomy & Astrophysics, 2010)
Aims. The ESO SN Ia Progenitor Survey (SPY) aims at finding merging double degenerate binaries as candidates for supernova type Ia (SN Ia) explosions. A white dwarf merger has also been suggested to explain the formation of rare types of stars like R CrB, extreme helium or He sdO stars. Here we present the hot subdwarf B binary GD 687, which will merge in less than a Hubble time. Methods. The orbital parameters of the close binary have been determined from time resolved spectroscopy. Since GD 687 is a single-lined binary, the spectra contain only information about the subdwarf primary and its orbit. From high resolution spectra the projected rotational velocity was derived. Assuming orbital synchronisation, the inclination of the system and the mass of the unseen companion were constrained. Results. The derived inclination is i = 39.3+6.2-5.6 °. The mass M2 = 0.71 -0.21+0.22 M⊙ indicates that the companion must be a white dwarf, most likely of C/O composition. This is only the fourth case that an sdB companion has been proven to be a white dwarf unambiguously. Its mass is somewhat larger than the average white dwarf mass, but may be as high as 0.93 M⊙ in which case the total mass of the system comes close to the Chandrasekhar limit. Conclusions. GD 687 will evolve into a double degenerate system and merge to form a rare supermassive white dwarf with a mass in excess of solar. A death in a sub-Chandrasekhar supernova is also conceivable. © ESO, 2010.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Stars: individual: GD 687; Stars: rotation; Subdwarfs; Supernovae: general